Investigation of lung tumour peripheral doses using normoxic polymer gel and film dosimetry techniques. (August 2019) - Venning, A; Mundayadan Chandroth, M; Chick, B; Waller, B; Morgan, C
Abstract: This paper describes the investigation of lung tumour peripheral doses for 6MV, 6MV FFF, 10MV FFF and 15MV conformal arc therapy (CAT) beams calculated in the Monaco® TPS and delivered using a flattening filter free capable Elekta® Agility TM linac. Two independent high resolution dosimetry techniques were used for investigations. Measurements were performed using the normoxic PAG polymer gel dosimeter and GAFchromic TM EBT3 film and compared against the calculated dose plane from the Monaco treatment planning system. Both measurement methodologies indicate that Monaco is overestimating the lung tumour peripheral dose for the beams investigated in this study. It is shown that when using 10MV FFF in lung for arc deliveries, there is a dosimetric compromise compared with 6MV and 6MV FFF.